Service Utopia: impact of hypermarket service extensions on corporate brand value based on consumer experience and brand personality - Hassan, Hasliza; Rahman, Muhammad Sabbir; Sade, Abu Bakar (American Scientific Publishers, 2015)
Hypermarket retailing is very well accepted by most people, especially those who are living in urban areas with a high population density. Parallel to the high acceptance, hypermarket retailers are continuously enhancing the retailing operation by offering better facilities for consumers within a modern self-service shopping concept as a service utopia. This conceptual research proposes the possible empirical study concerning the value of hypermarket service extensions that are offered through consumer shopping experience and brand personality. This research is mainly based on secondary findings through a review of the literature as well as through general observation at selected hypermarket retail outlets. It is expected that there is a correlation between consumer experience and brand personality. Both consumer experience and brand personality are expected to influence the hypermarket to offer service extension facilities, which will also stimulate the overall corporate brand value of a hypermarket. The proposed conceptual framework through this paper is expected to provide a solid path for discovering new knowledge within this field. It is also expected that this conceptual research will strengthen future empirical findings.